125 ARIPIPRAZOLE-INDUCED SYNDROME OF INAPPROPRIATE ANTIDIURETIC HORMONE SECRETION (SIADH). (1st January 2006) - Godkar, D.; Bachu, K.; Gasparyan, A.; Yakoby, M.; Niranjan, S.
Abstract : Background: Aripiprazole is a newer class atypical antipsychotic agent used for effective treatment of schizophrenia. It significantly reduces unwanted side effects of older counterpart typical antipsychotics by targeting, with high affinity, dopamine D2/D3 and serotonin 5-HT1A/5-HT-2A receptors. Its documented mechanism of action makes it an unlikely agent to cause SIADH. Case Report: We present a case of a patient with schizophrenia who after starting on aripiprazole developed SIADH on the sixteenth day of treatment. After medication was discontinued, SIADH resolved and the patient's serum sodium levels returned to normal in the following days. Our research indicates this to be the first reported case of SIADH induced by aripiprazole. Discussion: Antipsychotic medications, or neuroleptics, have revolutionized the treatment and prognosis of psychotic disorders, specifically schizophrenia, in the past century. The medications are of two groups based on mechanism: typical antipsychotics and newer atypical antipsychotics. The former exclusively block the dopamine D2 receptor in the brain, while the latter additionally block serotonin receptors to a limited extent. Atypical antipsychotics include clozapine, risperidone, olanzapine, quetiapine, and, recently, aripiprazole. Aripiprazole is unique to all other atypical antipsychotic medications in that its mechanism of action includes a partial agonism at several G-protein coupled receptors, specifically the dopamine D2/D3 and serotonin 5-HT1A receptors, and antagonistic action at other serotonin receptors, such as 5-HT2A. SIADH has not been documented in the literature as a side effect of aripiprazole. Teaching Point: Further studies are required to elucidate the exact mechanism of aripiprazole in causing SIADH. This case serves to remind clinicians to assess laboratory values and clinical symptoms after initiation of new psychotropic treatment to the patient, keeping in mind differential diagnoses, which are not necessarily documented side effects of the treatment.